Liquefaction-Induced Lateral Deformations Computational Assessment during Tohoku Earthquake. (5th August 2013) - Forcellini, Davide; Della Bartola, Fabio; Tarantino, Angelo Marcello
Abstract : Liquefaction-induced lateral spreading during Tohoku earthquake resulted in significant damage, and disruption of functionality for structures and life. The paper aims at reproducing this on-site evidence presenting the state of the art about the most credited qualitative approach and comparing these methods with numerical computation. In this regard, finite element (FE) simulations are increasingly providing a versatile environment in order to assess economical and effective damage. In the study, several systematic three-dimensional FE computations have been conducted to numerically evaluate the effects in terms of liquefaction-induced lateral deformations. The analysis is performed in correspondence with Urayasu City, where the registered liquefaction consequences on residential buildings were wide if compared with the ordinary seismic shake. This study can be used both for post-earthquake evaluations and for pre-earthquake vulnerability predictions.